Five-year cardiovascular outcomes in patients with chronic myeloid leukemia treated with imatinib, dasatinib, or nilotinib: A cohort study using data from a large multinational collaborative network - Nunes, Rafael Amorim Belo; Neves, Precil Diego Miranda de Menezes; da Costa, Leandro Menezes Alves; Bachour, Philip; Cantarelli, Marcelo José de Carvalho; Oliveira, Gustavo Bernardes de Figueiredo; Avezum Jr., Álvaro (Frontiers in Cardiovascular Medicine, 2023)
Background Breakpoint cluster region-Abelson gene (BCR-ABL) tyrosine kinase inhibitors (TKIs) have revolutionized the treatment of patients with chronic myeloid leukemia (CML). However, concern has arisen about the cardiac safety profile of these drugs. Objectives This study aims to compare long-term risks of adverse cardiovascular and cerebrovascular events (ACE), heart failure or left ventricular ejection fraction (LVEF) < 50%, and venous thromboembolic events (VTE) in patients with CML treated with BCR-ABL TKIs, using data from a large multinational network. Methods Patients aged ≥ 18 years with CML treated with imatinib, dasatinib, or nilotinib without prior cardiovascular or cerebrovascular disease were included. We used propensity score matching to balance the cohorts. The 5-year cumulative incidences and hazard ratios were calculated. Results We identified 3,722 patients with CML under treatment with imatinib (n = 1,906), dasatinib (n = 1,269), and nilotinib (n = 547). Patients with imatinib compared to dasatinib showed a higher hazard ratio (HR) for ACE (HR 2,13, 95% CI 1.15–3.94, p = 0.016). Patients with imatinib presented a lower HR than nilotinib for ACE (HR 0.50, 95% CI 0.30–0.83, p = 0.0074). In relation to heart failure or LVEF < 50%, patients with imatinib had a higher HR than dasatinib (HR 9.41, 95% CI 1.22–72.17, p = 0.03), but no significant difference was observed between imatinib and nilotinib (HR 0.48, 95% CI 0.215–1.01, p = 0.064). Conclusion In this retrospective study with a large number of patients with CML, those treated with nilotinib had a higher 5-year ratio of ACE, while patients with dasatinib showed a lower ratio than patients with imatinib. The ratio of heart failure was higher in patients with imatinib than in patients with dasatinib, but not when compared to nilotinib.